Complete genome sequence of Desulfohalobium retbaense type strain (HR100T). Issue 1 (January 2010) - Spring, Stefan; Nolan, Matt; Lapidus, Alla; Glavina Del Rio, Tijana; Copeland, Alex; Tice, Hope; Cheng, Jan-Fang; Lucas, Susan; Land, Miriam; Chen, Feng; Bruce, David; Goodwin, Lynne; et al.
Abstract Desulfohalobium retbaense (Ollivieret al. 1991) is the type species of the polyphyletic genusDesulfohalobium, which comprises, at the time of writing, two species and represents the familyDesulfohalobiaceae within theDeltaproteobacteria .D. retbaense is a moderately halophilic sulfate-reducing bacterium, which can utilize H2 and a limited range of organic substrates, which are incompletely oxidized to acetate and CO2, for growth. The type strain ${\rm HR}_{100}^{\rm T}$ was isolated from sediments of the hypersaline Retba Lake in Senegal. Here we describe the features of this organism, together with the complete genome sequence and annotation. This is the first completed genome sequence of a member of the familyDesulfohalobiaceae . The 2, 909, 567 bp genome (one chromosome and a 45, 263 bp plasmid) with its 2, 552 protein-coding and 57 RNA genes is a part of theG enomic E ncyclopedia of B acteria and A rchaea project.